Exclusive breastfeeding: its benefits from Islamic and scientific perspective - Zaifuddin Md Rasip; Rozeeda Kadri; Yasir Ramlee; Mostefa Yahi (Human Resource Management Academic Research Society (HRMARS), 2024)
Exclusive breastfeeding has become a pressing issue in modern society due to misconceptions and lack of awareness regarding its benefits. Despite its proven advantages, many mothers face challenges in adhering to exclusive breastfeeding practices. This study examines the advantages of breastfeeding from Islamic and scientific perspectives, focusing on its impact on maternal and infant health and its religious significance. Using a qualitative approach, data was gathered from books, journals, and academic articles. Recent and relevant sources were analyzed and categorized into key themes for this purpose. The findings highlight that breastfeeding provides optimal nutrition, protecting infants from illnesses such as respiratory and gastrointestinal infections and allergies. Exclusively breastfed infants display stronger immune systems and better cognitive development. From an Islamic perspective, breastfeeding is regarded as a maternal duty with spiritual rewards, fostering an emotional bond between mother and child. The Quran encourages mothers to nurse their children for up to two years, emphasizing its importance in Islamic teachings. This study aims to bridge the gap by integrating insights from Islamic teachings and scientific findings to promote a holistic understanding of exclusive breastfeeding. It also recommends exploring community education to raise awareness about the significance of exclusive breastfeeding among young mothers. By integrating scientific insights and religious guidance, a deeper understanding can enhance breastfeeding practices, benefiting both current and future generations. These efforts could address societal challenges and promote the well-being of mothers and children.